Association Study Between Polymorphic Loci in Cholesterol Metabolism Pathway and Gallstone in the Tibetan Population - Ma, Lifeng; Chen, Hui; Zhang, Zhiying; Liu, Lijun; Zhao, Yiduo; Li, Yansong; Zhao, Zhipeng; Chen, Haitao; Kang, Longli (Frontiers in Genetics, 2022)
Background: The incidence of gallstones in the Tibetan population is increasing rapidly. Previous studies indicated that genetic variation located in the cholesterol metabolism pathway may be associated with the incidence of gallstones. Methods: By recruiting 132 Tibetan gallstone patients and 52 normal Tibetan controls, we performed next-generation sequencing for 508 genes in the cholesterol metabolism pathway. Additionally, by integrating the sequence data of 41 normal Tibetan subjects in the public database, we finally obtained 93 normal Tibetan controls. Single nucleotide polymorphisms (SNPs) calling were performed by using the GATK pipeline. The quality control criteria for SNPs were: missing rate < 0.05; minor allele frequency (MAF) ＞ 0.01; and P value > 0.001 in the Hardy-Weinberg Equilibrium (HWE) test. To eliminate the influence of population heterogeneity, Principal Component Analysis (PCA) was carried out by using the smartpca software. Association analyses were performed by Plink software. Multiple tests were adjusted by the false discovery rate (FDR) method. Results: A total of 2,401 SNPs were obtained by analyzing 508 genes, and 2,011 SNPs left after quality control. After adjusting the eigen vectors, we found that 10 SNPs (SNV05997, rs80145081, rs80005560, rs79074685, rs748546375, rs201880593, rs142559357, rs750769471, rs869789 and rs4072341) were significantly associated with gallstone. Subsequently, by comparing the case group with our control group and the public database control group separately, we further found that the SNP rs869789 was consistently significantly associated with gallstone (P = 9.04×10-3 in cases vs. our controls and 5.73×10-3 in cases vs. public controls, respectively). Conclusions: By systematically analyzed SNPs in the cholesterol metabolism pathway, we identified one polymorphic locus rs869789 significantly associated with the pathogenesis of gallstone in the Tibetan population. This study will provide clue for further mechanism study of gallstone in the Tibetan population.